Audição e biomarcadores do metabolismo oxidativo em escolares de região fumicultora do Rio Grande do Sul - Kunst, Letícia Regina (2013)
Objective: to evaluate the auditory system and the oxidative metabolism of students who lived in a tobacco-producing region. Methods: 21 normal-hearing students from the tobacco-producing region, study group (SG), and 25 normal-hearing students who did not live in the countryside, control group (CG), participated of this research. The auditory system was evaluated by the distortion-product otoacoustic emissions (DPOAE) and by the suppression of DPOAE. The biomarkers of oxidative metabolism were: comet assay, micronuclei test (MN), dichlorofluorescein diacetate (DCFH-DA) for the rate of free radicals and fluorimetric assay for the quantitation of DNA. The data were exposed to statistical analysis. Results: The students of both groups revealed DPOAE presented. A significant difference was detected between groups in relation to the right ear (RE) in the frequency of 4000 Hz and to the left ear (LE) in the frequency of 2000 Hz, with a mean of SG lower than the one found for the CG. Considering the mean of both ears, the SG presented lower mean among all the frequencies and it was found a significant difference in the frequencies of 2000 and 4000 Hz. Considering the overall mean of DPOAE by ear, it was observed no significant differences. In relation to the occurrence of suppression, the individuals of both groups showed suppression effect of DPOAE presented. By comparing the occurrence of suppression of DPOAEs, between groups, no statistically significant association was detected. Concerning the biomarkers of oxidative metabolism: the comet assay, the rate of production of free radicals and fluorimetric assay for quantitation of DNA; the mean of the SG was significantly higher than the one found in the CG. In the MN test, it was found a significant difference in the sum of abnormal cells and the frequency of binucleated cells, with the mean of the SG higher than the mean of the CG. And, in relation to the frequency of cells with MN, it was verified no significant difference between both groups. It was verified an association between amplitudes and biomarkers of oxidative metabolism, but as the suppression of DPOAE this association was not observed. Conclusion: Both groups revealed DPOAE and suppression effect of DPOAE presented, but the SG showed a decrease in mean amplitudes at all frequencies. The SG showed a significantly higher index in all biomarkers of oxidative metabolism. It was verified association between level response of DPOAE and the results of the oxidative metabolism verification tests.